1992
DOI: 10.1111/j.1365-313x.1992.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic sugarcane plants via microprojectile bombardment

Abstract: SummaryTransgenic sugarcane plants were produced by bombardment of embryogenic callus with high-velocity DNA-coated microprojectiles, followed by a selection and regeneration procedure designed for this target tissue. Optimal bombardment conditions for embryogenic callus required microprojectile velocities higher than those previously found effective for sugarcane suspension culture cells. Bombardment of target tissues twice increased the number of transiently expressing cells in regenerable callus regions, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
147
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(149 citation statements)
references
References 31 publications
0
147
0
2
Order By: Relevance
“…A expressão transiente de genes exógenos em protoplastos e a expressão estável em calos foram descritas por , utilizando eletroporação. Plantas transgênicas foram obtidas através da utilização de métodos diretos e indiretos de transformação, incluindo a eletroporação de tecidos meristemáticos (Arencibia et al 1992) e fragmentos de calo (Arencibia et al 1995), o bombardeamento de calos embriogênicos (Bower & Birch 1992, Gallo-Meagher & Irvine 1996 e outras técnicas baseadas na utilização da Agrobacterium tumefaciens (Arencibia et al 1997, Enríquez-Obrigón et al 1998.…”
Section: Introductionunclassified
“…A expressão transiente de genes exógenos em protoplastos e a expressão estável em calos foram descritas por , utilizando eletroporação. Plantas transgênicas foram obtidas através da utilização de métodos diretos e indiretos de transformação, incluindo a eletroporação de tecidos meristemáticos (Arencibia et al 1992) e fragmentos de calo (Arencibia et al 1995), o bombardeamento de calos embriogênicos (Bower & Birch 1992, Gallo-Meagher & Irvine 1996 e outras técnicas baseadas na utilização da Agrobacterium tumefaciens (Arencibia et al 1997, Enríquez-Obrigón et al 1998.…”
Section: Introductionunclassified
“…Although transformation of maize (Fromm eta/., 1990; Gordon-Kamm eta/., 1990; Rhodes et al, 1988) and sugarcane (Bower and Birch, 1992) has been reported, neither system is efficient enough to support the analysis of a large number of gene constructions over a reasonably short time period.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the biolistic method has emerged LS a simple and promising alternative for cereal transformation, and has been successfully used in maize, rice, sugarcane and whoat transformation (Fromm et al 1990; Gordon-Kamm et uf. Christou et al 1991;Bower and Birch, 1992;Vasil et al 1992). Procedures using organized tissues such as immature embryos (Christou et al 1991) or embryo slices (Cao et al 1991) as target tissues for rice transformation may make the system less genotype-dependent.…”
Section: Introductionmentioning
confidence: 99%